2015
DOI: 10.1128/jvi.02897-14
|View full text |Cite
|
Sign up to set email alerts
|

Impact and Regulation of Lambda Interferon Response in Human Metapneumovirus Infection

Abstract: Human metapneumovirus (hMPV) is a respiratory paramyxovirus that is distributed worldwide and induces significant airway morbidity. Despite the relevance of hMPV as a pathogen, many aspects of the immune response to this virus are still largely unknown. In this report, we focus on the antiviral immune response, which is critical for viral clearance and disease resolution. Using in vitro and in vivo systems, we show that hMPV is able to induce expression of lambda interferon 1 (IFN-1), IFN-2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 55 publications
(93 reference statements)
4
62
3
Order By: Relevance
“…14 All the four studies described above have used primer sets where at least one of the primers binds to the exon/intron/exon-intron junctions (Figure 4b). Using a primer set that uniquely binds to the 3′-untranslated region of IFNL4 mRNA, IFN-λ4 induction was seen at levels similar to that of IFN-λ2/3, upon human metapneumovirus infection of A549 cells by Banos-Lara et al 45 We used the same primer set and found similar high expression levels upon poly(I:C)/HCV RNA transfection in A549 cells. 89 Two other studies have reported no such problems in amplifying IFNL4 transcripts from liver biopsies.…”
Section: Transcription Studies On the Ifnl4 Genesupporting
confidence: 59%
See 1 more Smart Citation
“…14 All the four studies described above have used primer sets where at least one of the primers binds to the exon/intron/exon-intron junctions (Figure 4b). Using a primer set that uniquely binds to the 3′-untranslated region of IFNL4 mRNA, IFN-λ4 induction was seen at levels similar to that of IFN-λ2/3, upon human metapneumovirus infection of A549 cells by Banos-Lara et al 45 We used the same primer set and found similar high expression levels upon poly(I:C)/HCV RNA transfection in A549 cells. 89 Two other studies have reported no such problems in amplifying IFNL4 transcripts from liver biopsies.…”
Section: Transcription Studies On the Ifnl4 Genesupporting
confidence: 59%
“…30 Some of the other IFN-λs are known to be induced by several human pathogens including M. tuberculosis, 42 human papilloma virus, 43 influenza virus 44 and human metapneumovirus (also induces IFN-λ4), 45 and have clear antiviral activities against some but not other viruses in mice (reviewed in ref. 46).…”
Section: Genetic Association Of Ifnl Locus Polymorphisms Is Not Limitmentioning
confidence: 99%
“…In most studies, cultured cells were treated with IFN-λs and the impact of viral infection was assessed. These studies investigated human (66) and murine CMV (59), dengue virus (114,145), encephalomyocarditis virus (28,29,146), herpes virus type 2 (120), hepatitis B virus (115), HCV (37,60,113,115,116,147), HIV (40,117,118), human meta pneumovirus (121), influenza virus (122,(148)(149)(150)(151)(152), (128,153,154), sendai virus (155)(156)(157), and vesicular stomatitis virus (131,158,159).…”
Section: Viral Infectionsmentioning
confidence: 99%
“…This modified virus is a sensitive reporter of productive infection in live cells. Notably, hMPV both elicits and is sensitive to IFN-mediated anti-viral response [32]. As a cytolytic virus, we chose a variant of the epizootic hemorrhagic disease virus (EHDV), an orbivirus that naturally infects ruminants and is transmitted by biting midges [33].…”
Section: Introductionmentioning
confidence: 99%